Development of Interactive Multimedia Through Realistic Mathematics Education Approach Assisted by Articulate Storyline - Wahyuni, Fina Tri; Adiyanto, A. Sahrul; Syifa, Zahra As (Universitas Islam Negeri Sunan Kudus, 2025)
The purpose of this research is to develop interactive multimedia based on the Realistic Mathematics Education (RME) approach with Articulate Storyline, on the topic of Systems of Linear Equations in Two Variables (SPLDV), and to determine the validity and practicality of the product. This research employed the Research and Development (R&D) method using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). A small-scale trial involved with six students, and a large-scale trial was conducted with 26 eighth-grade students from MTs Urwatil Wutsqo Jepara. The results indicated that the interactive multimedia based on the RME approach supported by Articulate Storyline for SPLDV was highly valid and very practical for instructional use. The Evaluation by content experts resulted in an overall percentage score of 86.25% in the